2017
DOI: 10.1007/s00431-016-2843-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pneumococcal conjugate vaccine on community-acquired pneumonia hospitalizations in children with comorbidity

Abstract: The burden of community-acquired pneumonia (CAP) in high-income countries is still significant. The introduction of pneumococcal conjugate vaccines (PCV) has reduced the overall need for hospitalization for CAP. However, it is not clear whether children with underlying disease also have benefitted from the PCV immunization programme. Children 0 to <5 years of age hospitalized with CAP and discharged with an ICD-10 code of J13-J18.9 between November 1, 2005, and April 30, 2007 (pre-vaccination period), and Nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…34 Pneumococcal vaccination also reduces the number of hospitalizations due to IPD in patients with comorbidities, such as cancer. 35 Moreover, a study in adults showed that influenza and pneumococcal vaccinations were immunogenic when administered early in the course of disease, ideally 4 to 6 weeks (at least 2 weeks) before starting the chemotherapy and, if not possible, 3 months after the end of chemotherapy. 36 Several other studies suggest that vaccination with PCV13 directly after completion of chemotherapy is safe and highly effective to prevent IPD without age restriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Pneumococcal vaccination also reduces the number of hospitalizations due to IPD in patients with comorbidities, such as cancer. 35 Moreover, a study in adults showed that influenza and pneumococcal vaccinations were immunogenic when administered early in the course of disease, ideally 4 to 6 weeks (at least 2 weeks) before starting the chemotherapy and, if not possible, 3 months after the end of chemotherapy. 36 Several other studies suggest that vaccination with PCV13 directly after completion of chemotherapy is safe and highly effective to prevent IPD without age restriction.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that children undergoing therapy for an ALL have a relative risk of 11.4 times of developing an invasive pneumococcal disease (IPD) during the first 2 years post-cancer diagnosis compared with healthy children 34 . Pneumococcal vaccination also reduces the number of hospitalizations due to IPD in patients with comorbidities, such as cancer 35 . Moreover, a study in adults showed that influenza and pneumococcal vaccinations were immunogenic when administered early in the course of disease, ideally 4 to 6 weeks (at least 2 weeks) before starting the chemotherapy and, if not possible, 3 months after the end of chemotherapy 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The comorbidities included were asthma (ICD-9-CM: 493), diabetes mellitus (DM) (ICD-9-CM: 450), chronic lung disease (ICD-9-CM: 770.7), heart failure (ICD-9-CM: 428), epilepsy (ICD-9-CM: 345), and chronic kidney disease (CKD) (ICD-9-CM: 580∼589), diagnosed once at hospitalization or at least thrice in the outpatient department in 1 year. These medical conditions were proved to be risk factors of pneumonia (18,19). The propensity score was calculated using the Statistical Analysis System 9.4 program (SAS Institute, Cary, North Carolina, USA).…”
Section: Sampled Participantsmentioning
confidence: 99%
“…Many pathogens are responsible for CAP in children, including Streptococcus pneumonia and Haemophilus influenzae . Several viral pathogens have also been acknowledged as important pathogens for CAP, including influenza virus, respiratory syncytial virus, and adenoviruses [ 5 ]. In any case, it must be considered that conventional microbiological studies can identify the etiology in only a limited number of patients [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%